A Practical Recommendation for Teaching Neck Anatomy During Neck Dissection in the Operating Room. Issue 4 (June 2018) - Çelik, Mehmet; Çomoğlu, Şenol; Yağci, Ibrahim; Aydemir, Levent; Altun, Demet; Kiyak, Erkan
Abstract : Abstract: Anatomy knowledge is not only essential for surgeons but also has importance for anyone who performs an invasive procedure on a patient, and provides examination and diagnosis of patients and sharing of these findings to the patient and other medical professionals. It is accepted that most surgical procedures could facilitate anatomic perception in surgical internships. There is an educational tendency to explore innovative instructional tools and methods that can help support current education styles. This study investigates the effect of a green laser pointer on students' perceptions and educational effectiveness when neck dissection is performed in the operating room.